Voluntary physical activity mitigates alveolar bone loss in mice with ligature-induced experimental periodontitis. (August 2022) - Bertolini, Natalia O.; Pereira, Gustavo J.S.; Silva, Viviam O.; de Molon, Rafael Scaf; Morari, Joseane; Velloso, Lício A.; Andrade, Eric F.; Pereira, Luciano J.; Moura, Rodrigo F.
Abstract: Objective: To investigate the effect of voluntary physical activity (VPA) on inflammatory profile and the progression of experimental periodontal disease (PD) in mice. Methods: Male C57BL/6 mice were randomly distributed into Control; VPA; PD and PD/VPA groups. We registered VPA (total volume of revolutions) and average speed (revolutions/minute) in a free running wheel for 30 days. On the 15th day, animals from the PD and PD/VPA groups received ligatures on the upper second molars bilaterally. On the 30th day animals were euthanized, and PD progression was assessed by measuring alveolar bone loss (ABL - the linear distance between the cemento-enamel junction and the alveolar bone crest on the teeth buccal surface). Gene expression of RANKL (kappa nuclear factor B receptor) OPG (osteoprotegerin), IL-1β (interleukin 1 beta), IL-6 (interleukin 6) and TNF-α (tumor necrosis factor alpha) were evaluated by real-time PCR (quantitative Polymerase Chain Reaction - relative gene expression). Results: The total volume of physical activity and the activity speed decreased along the seven days after ligature-placement (p < 0.05), returning to a similar pattern in relation to VPA group. Ligature placement produced significant bone resorption, and increased RANKL, IL-1β, IL-6 and TNF-α expression. VPA reduced ABL (p < 0, 05) and the expression of TNF-α and IL-1β, whereas increased OPG expression. Conclusion: Animals induced to PD with access to the VPA wheel presented both lower gingival inflammation and less alveolar bone resorption in comparison to animals without access to the wheel.